2018
DOI: 10.1001/jama.2018.7855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fruquintinib vs Placebo on Overall Survival in Patients With Previously Treated Metastatic Colorectal Cancer

Abstract: IMPORTANCE Patients with metastatic colorectal cancer (CRC) have limited effective and tolerable treatment options.OBJECTIVE To evaluate the efficacy and safety of oral fruquintinib, a vascular endothelial growth factor receptor (VEGFR) inhibitor, as third-line or later therapy in patients with metastatic CRC. DESIGN, SETTING, AND PARTICIPANTS FRESCO (Fruquintinib Efficacy and Safety in 3+ LineColorectal Cancer Patients) was a randomized, double-blind, placebo-controlled, multicenter (28 hospitals in China), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
235
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 250 publications
(273 citation statements)
references
References 21 publications
11
235
3
Order By: Relevance
“…If patients were previously diagnosed with CRC outside the selected hospitals, the initial diagnosis dates, if available, were used as the primary diagnosis dates. As a previous phase III clinical trial suggested that the maximum period of the 3rd line treatment usage was nine months [21], in this study, patients who started third-line chemotherapy after January 1, 2016 were excluded to allow a minimum nine-month observation period for the entire third-line chemotherapy to be documented.…”
Section: Study Populationmentioning
confidence: 99%
“…If patients were previously diagnosed with CRC outside the selected hospitals, the initial diagnosis dates, if available, were used as the primary diagnosis dates. As a previous phase III clinical trial suggested that the maximum period of the 3rd line treatment usage was nine months [21], in this study, patients who started third-line chemotherapy after January 1, 2016 were excluded to allow a minimum nine-month observation period for the entire third-line chemotherapy to be documented.…”
Section: Study Populationmentioning
confidence: 99%
“…9 In this case, the patient experienced disease progression during the first-line FOLFIRI plus cetuximab treatment, and after taking afatinib, achieved 3-month progression free. Compared with the median PFS of other molecule-targeting drugs for mCRC third-line treatment, like regorafenib (1.9months) 22 , trifluridine-tipiracil (TAS-102, 2.0months) 23 and fruquintinib (3.7months) 24 , afatinib brought more impressive benefit for this HER2-amplified mCRC patient.…”
Section: Discussionmentioning
confidence: 88%
“…104 Several other novel agents are being investigated as third-line or later-line treatment options for mCRC. 3 Tyrosine kinase inhibitors, such as famitinib (NCT02390947), fruquintinib, 105 and anlotinib (NCT02332499), are under investigation in phase III trials. The alkylating agent temozolomide showed some activity in phase II studies of patients with mCRC and O 6 -methylguanine DNA methyltransferase (MGMT) promoter methylation, 106,107 even though molecular selection might be further improved leaving the latter approach under investigation.…”
Section: Discussionmentioning
confidence: 99%